Perancangan Prototype Sistem Monitoring Pemberian Pakan Ternak Ikan Berbasis Internet of Things - Mutaqien, Rizky; Supriatna, Asep Deddy (Institut Teknologi Garut, 2025)
Manual fish feeding activities often lead to issues such as irregular feeding schedules and uncontrolled feed quantities, which can negatively impact fish growth and health. This study aims to design an automatic fish feeding system using the ESP32 microcontroller, Blynk application, water level sensor, and HC-SR04 ultrasonic sensor. The system is designed to automatically dispense feed based on water level measurements. The study applies the Rational Unified Process (RUP) methodology, which involves four main phases: Inception, Elaboration, Construction, and Transition. In the Inception phase, system requirements and initial planning are identified. The Elaboration phase includes detailed analysis and design, such as hardware component selection and system design. In the Construction phase, the system is implemented using the PHP programming language. The Transition phase involves final testing using blackbox testing. The results show that the system successfully connects the microcontroller to WiFi and the Blynk application, enabling effective remote control. The water level sensor and HC-SR04 ultrasonic sensor function well in detecting water levels, and the system can automatically dispense feed based on sensor readings and the set schedule. Testing indicates that the system is reliable and flexible, with potential for further improvement through more accurate sensor calibration and additional sensor integration. Suggestions for future development include optimizing power consumption, enhancing connection security, and developing additional monitoring features to provide more comprehensive and responsive control. Therefore, this automatic fish feeding system offers an efficient and practical solution for fish maintenance, allowing users to manage feeding automatically.